Status Hak Milik Atas Tanah di Kawasan Wilayah Register berdasarkan Hukum Positif - Furyani, Sri; Salim, Choirul (Bulletin of Community Engagement, 2024)
Ownership of occupied land is important for indonesian citizens to be able to guarantee legal certainty and as legal protection for those who inhabit an area. Therefore, to be able to guarantee legal certainty and as legal protection, Indonesian citizens must register the land they occupy. So what if a place that has many inhabitants and permanent buildings (a village has been formed) in in the production forest area of register 47 way terusan? This research uses a normative-empirical method which is a research method that combines normative legal elments which are then supported by the addition of empirical element data. There are two types of data, namely primary data and secondary data. Data collection techniques use interviews and documentation and the analysis used is descriptive. The nature of description or explanation of the subject and object of research. The results showed that the construction of community settlements violated the rules based on the law of the republic of Indonesian number 41 of 1999 concerning forestry, while it is allowed to make community settlements must submit applications outside the use of forest areas in accordanc with the regulation of the minister of environment and forestry number 7 of 2021 concerning planning, changes in forest area designation and changesin forest area functions and use of forest areas, in carrying out research, researchs obtained data showing that the register 47 way terusan forest area is a forestry partnership with a total of 29 forest farmers groups (KTH). Production Forest Area Register 47 Way Terusan Located In Mataram Udik Villages, Bandar Mataram Sub-District, Central Lampung District Is A Production Forest Area Register 47 Way Terusan Based On Decre (SK) Number 316/Menhut-II/2005 Which Designates Production Forest Area Register 47 As KPHP Area With An Area Of Approximately 12.500 Hectares Keywords: Land Ownership Status, Positive Law, Legal Protection